Augmented Reality: Challenges, Opportunities and Implementation in the Tourism Industry - Achmad Solechan; Yuli Fitrianto; Haryo Kusumo (An International Journal Tourism and Community Review, 2024)
It is important to carry out this research because the digital tourism theme is a theme that is still relatively little carried out by other researchers. This research uses qualitative methods with literature review techniques with the results discussing 37 research article publications that are relevant to this research. The research results show that the application of digital tourism has a lot of potential that can change the way the tourism industry operates and interacts with tourists, including increased accessibility, enhanced tourism experiences based on AR and VR technology, and effective marketing. The application of Digital Tourism opens up various interesting opportunities in the tourism industry, including: digital marketing, virtual tourist experiences with AR and VR, tour guide applications, online booking, tourism data analysis, environmental conservation, and personalization of tourist experiences.The development or trend of digital tourism in 4 eras has apparently experienced a significant increase. Some of the challenges faced related to Digital Tourism include: lack of a comprehensive framework, limited understanding of technology users, the need to measure the sustainable impact of digital technology, data privacy and security issues, long-term impacts of digital tourism use, collaboration with parties involved in digital tourism, cross-cultural perspectives and implementation of management strategies using intelligent systems.